(untitled) (Bangladesh Journal of Nuclear Medicine, 2018)
Congenital lymphedema is the rarest form of primary lymphedema, accounting for approximately 1: 60,000 live births. Congenital lymphedema can be classified into familial (hereditary) and idiopathic (non hereditary) subgroups. When congenital lymphedema is of the hereditary form the eponym Milroy disease is applied. Lymphedema without any dysmorphic features and no family history of lymphedema the eponym idiopathic congenital lymphedema is utilized. Etiology of idiopathic primary congenital lymphedema is unknown and a de novo genetic event of genes involved in lymphangiogenesis is a possibility. Radionuclide lymphoscintigraphy is considered as a gold standard for the diagnosis of lymphedema. This reported interesting case was an eleven months old girl having swelling of right lower limb since birth. There was no family history of lymphedema and no any dysmorphic features consistent with Milroy disease. The primary diagnosis was congenital lymphedema of idiopathic (non hereditary) subtype. Lymphoscintigraphic with Technetium-99m (Tc- 99m nanocolloid) revealed no lymphatic channels or inguinal lymph nodes on right side in early or delayed images up to 2 hours views and the diagnosis of primary idiopathic congenital lymphedema was confirmed. Bangladesh J. Nuclear Med. 18(2): 183-185, July 2015